Ricci Curvature of Certain Submanifolds in Kenmotsu Space Forms (Communications in Mathematical Research, 2021)
In this paper, we obtain some sharp inequalities between the Ricci curvature and the squared mean curvature for bi-slant and semi-slant submanifolds inKenmotsu space forms. Estimates of the scalar curvature and the $k$-Ricci curvature,in terms of the squared mean curvature, are also proved respectively.